Pesticides: children at risk! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
In Benin, a study on pesticide users showed that more than three-quarters are young people, who do not yet know the nature of the products they are using, nor the content of the instructions on the labels. In fact, almost half the farmers in Benin...